2017
DOI: 10.3311/ppci.8698
|View full text |Cite
|
Sign up to set email alerts
|

New Formulations for Dynamic Behavior of Sand-Waste Tire Mixtures in a Small Range of Strain Amplitudes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Some of these factors can be assessed by state of the art laboratory investigations e.g. Torsional Simple Shear (TOSS), [5], Resonant Column [6], [7], or Bender Element [8] testing. Results of such investigations are used to improve existing material models or create new models, which represent more aspects of the real behavior than earlier ones.…”
Section: Small Strain Stiffness Of Soilsmentioning
confidence: 99%
“…Some of these factors can be assessed by state of the art laboratory investigations e.g. Torsional Simple Shear (TOSS), [5], Resonant Column [6], [7], or Bender Element [8] testing. Results of such investigations are used to improve existing material models or create new models, which represent more aspects of the real behavior than earlier ones.…”
Section: Small Strain Stiffness Of Soilsmentioning
confidence: 99%
“…On the other hand, some researchers have argued and demonstrated that the aforementioned parameters have a great influence on the serviceability behavior under normal loads and dynamic loads, and reduce vibrations in structures due to the high damping behavior of rubber. (Tsang et al, 2010;Edincliler et al, 2013;Boominathan et al, 2015;Chenari et al, 2017;Edincliler and Toksoy, 2017;Edincliler et al, 2018;Awlla et al, 2020). Ahmed (1992) investigated the properties of sand-tire chips by performing triaxial test.…”
Section: Introductionmentioning
confidence: 99%